(untitled) (Research, Society and Development, 2021)
The availability of professionals is a challenging factor for the management of health resources, especially in Brazil, a country with a process of interiorization and urbanization that differs between regions. The distribution of Brazilian physiotherapists is still poorly studied. Georeferencing is the conversion of the description of a location to a position on the Earth’s surface and is a useful tool in locating human resources in health. Thus, the objective was to analyze the distribution of physiotherapists in the Brazilian territory through the mapping of these professionals in the Regional Councils of Physiotherapy and Occupational Therapy and federative units. Descriptive documental study, number of physical therapists per Regional Council established by consulting official electronic portals or requesting data by e-mail from the Councils. The number of physiotherapists per 10,000 inhabitants was calculated, that is, a proportion of the distribution of physiotherapists according to the states and also for each Regional Council. For the construction of the map, it was used in GeoDa version 1.18.0. There was an increase in the number of professionals compared to previous studies, with a predominance of professionals in the Southeast, Northeast and South. These disparities can be associated with the level of urbanization, total population and regional aging rate.